PEMANFAATAN SITUS CANDI BELAHAN SEBAGAI SUMBER BELAJAR KONTEKSTUAL DALAM PEMBELAJARAN IPAS SEKOLAH DASAR - SYAIFUDIN, ACHMAD; SRI HARIANI, LILIK; RUSNO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Natural and Social Sciences (IPAS) learning in the Merdeka Curriculum emphasizes the application of contextual learning which utilizes local potential as an authentic learning source. However, the implementation of learning in elementary schools, especially SDN Wonosunyo I, Gempol District, Pasuruan Regency, is still dominated by the use of textbooks so that the use of surrounding cultural sites, such as Candi Belahan as a learning resource, is not yet optimal. The gap between the site's potential and learning practices, as well as the weak understanding and learning outcomes of students, drives the urgency of developing innovative learning strategies based on authentic learning resources. This research aims to implement and analyze the use of Candi Belahan as a media and contextual learning resource in science and science learning, especially class VI. The focus is to identify improvements in students' learning abilities, as well as revealing the value of character education and meaningful learning that is built. This research uses a qualitative approach with a case study method. Data collection was carried out through observation, interviews and document analysis at SDN Wonosunyo I, Gempol District, Pasuruan Regency. Data analysis is inductive to understand the process, obstacles, supporters and impacts of implementation in depth and holistically. Research findings reveal the formation of a mutually reinforcing cycle of improvement between three aspects, namely the creation of meaningful learning for students, the internalization of cultural values ​​and character, and the development of teacher professionalism. This cycle is driven by contextual learning at the cultural site and creates a sustainable transformation in the learning culture at the school.